KECANDUAN GAME ONLINE DAN PENYESUAIAN SOSIAL SISWA DI MA MUHAMMADIYAH PEKANBARU - Desri Rama; Elni Yakub; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Social adjustment is an important in teenage life. Especially for students who are addicted to online games. The purpose of this research is to determine the image of online game addiction and social adjustment of students in school. Addicted online game students is who she/he play online games more than two hours. The subjects of this research are students who addicted to online games as much as 12 people by using purposive sampling and this research method is a descriptive quantitative. In this study the instrument used is a questionnaire. The results of the study found that in general the students know online games from their friends, in a day of students playing online games for 3 to 4 hours, funds in playing online games as much as Rp. 10,000 to Rp. 15,000 in a day, while for the type of game played war genre. The impact students feel due to playing online games is eye irritation, numbness or tingling hands and feelings want to get angry. The social adjustment of students who are addicted to online games is less good. In the aspect of real appearance are, generally many students who violate the rules of the school such as unplug in school hours, on the adjustment aspects of the group generally students play only with certain groups such as playing with fellow game fans. In generally at aspects of social attitudes, students prefer to play online games rather than actively participate in extracurricular activities at school, and on the personal satisfaction aspect students feel less satisfied when doing something alone.Keywords: Online Game Addiction, Social Adjustment.